Testing the Frequency Response Control Function of Level-Dependent Earplugs - Emil Kozlowski; Rafal Mlynski; Krzysztof Lada (Applied Sciences)
Noise and the use of hearing protectors can impair the perception of useful sound at work. One solution to this problem is the use of hearing protectors with electronic systems. The aim of this article was to present the results of tests that verified the ability of the filters implemented in earplugs to control the frequency response. Tests were conducted to verify the implementation of digital filters in the sound processor. The filtration method proposed in octave bands with center frequencies of 125 Hz, 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz and 8000 Hz was fully sufficient. A high degree of compliance of the characteristics of the implemented solution with the standardized characteristics was observed. Measurements using an acoustic signal also confirmed the filters were correctly implemented in the designed earplugs. The filters attenuated the sound to about 30–40 dB. The obtained results allowed us to conclude that the developed earplugs can be used in the future to protect employees against noise, and, at the same time, effectively deliver useful signals to their user.